TEACHERS' PERSPECTIVES ON THE USE OF VIRTUAL INFORMAL ENVIRONMENTS IN THE PANDEMIC CONTEXT - Türkmen, Hakan; Kaplan, Gülçin; Sürgit, Cansu (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2024)
Since the pandemic situation, there has been a need for enacting student-centered teaching activities to make distance education more effective.